Evaluation of Seismic Events Occurred after Filling and Drawdown of the Reservoir at Song Tranh 2 HPP in Vietnam - Trinh, Nghia Quoc; Panthi, Krishna Kanta (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Reservoir-induced earthquakes are a challenging issue for hydropower, and have occurred at many sites around the world. However, each event is unique in itself and depends on the geo-tectonics and geo-hydrology of the area in which the event is situated. This article focuses on seismic events at the Song Tranh 2 hydropower project located in Quang Nam province, Vietnam. The construction of the 96 meter high Roller Compacted Concrete (RCC) dam of this project was completed in August 2011. Approximately one year after commissioning, the dam began experiencing a serious leakage problem through the dam body. In addition, a series of earthquakes occurred near the project area, and continued for several months. The high intensity and magnitude of the earthquakes caused damage to the project and promoted fear among the local people living in the downstream valley. The issues drew significant media attention and thousands of articles about this project were written within a short time. As a result, dam authorities have been subject to extreme public pressure.This paper describes the earthquake events and difficult situation that both the local population and authorities faced in its aftermath. In addition, we analyze seismic events qualitatively,using data and information on the water filling and drawdown processes. Our analysis provides an insight into these seismic events, as we reconstruct the earthquake scenarios and test a hypothesis of earthquake occurrence. Future earthquake activities are also predicted and compared. DOI: http://dx.doi.org/10.3126/hn.v15i0.11285 HYDRO Nepal Journal Journal of Water, Energy and Environment Volume: 15, 2014, July Page: 16-20